2014
DOI: 10.1111/cas.12569
|View full text |Cite
|
Sign up to set email alerts
|

Methylation‐induced downregulation of TFPI‐2 causes TMPRSS4 overexpression and contributes to oncogenesis in a subset of non‐small‐cell lung carcinoma

Abstract: We identified transmembrane protease, serine 4 (TMPRSS4) as a putative, druggable target by screening surgically resected samples from 90 Japanese non-small-cell lung cancer (NSCLC) patients using cDNA microarray. TMPRSS4 has two druggable domains and was upregulated in 94.5% of the lung cancer specimens. Interestingly, we found that TMPRSS4 expression was associated with tissue factor pathway inhibitor 2 (TFPI-2) expression in these clinical samples. In contrast to TMPRSS4, TFPI-2 expression was downregulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Hamamoto et al , have shown that TMPRSS4 is upregulated in NSCLC by epigenetic silencing of the tissue factor pathway inhibitor-2 [23]. We now provide evidence showing epigenetic changes that elicit TMPRSS4 promoter hypomethylation in NSCLC.…”
Section: Discussionsupporting
confidence: 63%
“…Hamamoto et al , have shown that TMPRSS4 is upregulated in NSCLC by epigenetic silencing of the tissue factor pathway inhibitor-2 [23]. We now provide evidence showing epigenetic changes that elicit TMPRSS4 promoter hypomethylation in NSCLC.…”
Section: Discussionsupporting
confidence: 63%
“…1 ). Among these, 5 DEGs were found to be significantly overexpressed in LUAD, and TMPRSS4, a gene contributing to oncogenesis in NSCLC, was selected as our target gene ( 17 , 19 ).…”
Section: Resultsmentioning
confidence: 99%
“…Because of this broad expression profile in cancer, TMPRSS4 has been a focal point of anti-cancer research in recent years. TMPRSS4 has been shown to promote proliferative processes in lung and thyroid cancer cells, while shRNA targeting of TMPRSS4 transcripts causes reductions in proliferation (Guan et al, 2015; Hamamoto et al, 2015; de Aberasturi et al, 2016). Work using cultured lung cancer cells demonstrated that TMPRSS4 promotes a mesenchymal and invasive phenotype, suggesting a role for epithelial to mesenchymal transition (EMT) (de Aberasturi et al, 2016).…”
Section: Tmprss2 and Tmprss4mentioning
confidence: 99%
“…Several reports have suggested that TMPRSS4 associates with poor prognosis and survival in a variety of different cancers (Cheng et al, 2013a,b; Wu et al, 2014; de Aberasturi and Calvo, 2015; Wang et al, 2015), which may be a result of an increase in the CSCs population, although the factors leading to TMPRSS4 upregulation are still not identified. One recent finding suggests that increased TMPRSS4 in cancer may result from gene-silencing of tissue factor pathway inhibitor 2 (TFPI-2), a consequence of improper methylation (Hamamoto et al, 2015). However, the mechanism which connects TFPI-2 and TMPRSS4 expression remains unknown.…”
Section: Tmprss2 and Tmprss4mentioning
confidence: 99%